2006
DOI: 10.1385/ct:6:1:51
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Hemodynamic Parameters and ECG in Healthy, Conscious, Freely Moving Telemetrized Beagle Dogs

Abstract: Interpretation of the dynamic cardiovascular parameters on safety pharmacology studies is a challenging process; sometimes, it is difficult to separate normal physiological variations from the effects of the test drug. Data from healthy control Beagle dogs (41 males and 25 females) implanted with telemetry transmitters (DSI, St. Paul, MN) from 34 studies performed from 2003 to 2005 were analyzed. Telemetry data were collected for a 30-s period every 10 min for 24 h after sham dosing. One-hour averages were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 21 publications
3
8
0
1
Order By: Relevance
“…In addition, the question of whether BP oscillates over the 24-h span in dogs is still a matter of debate (Miyazaki et al 2002;Piccione et al 2005;Soloviev et al 2006;Mochel et al 2013aMochel et al , 2014a. Results from our research (Mochel et al 2013a) showed that plasma renin (Fig.…”
Section: Components Of the Renin Cascade Blood Pressure And Urinarymentioning
confidence: 75%
“…In addition, the question of whether BP oscillates over the 24-h span in dogs is still a matter of debate (Miyazaki et al 2002;Piccione et al 2005;Soloviev et al 2006;Mochel et al 2013aMochel et al , 2014a. Results from our research (Mochel et al 2013a) showed that plasma renin (Fig.…”
Section: Components Of the Renin Cascade Blood Pressure And Urinarymentioning
confidence: 75%
“…The pens were cleaned twice a day. The swine were fed a diet (90.44% dry weight) containing 14.7% of protein, 3.1% of fat, 4.7% of crude protein, 6.06% of ash, 0.5% of salt (NaCl), 1.05% of calcium, 0.77% of phosphorus, 0.62% of lysine, 0.24% of methionine, 0.3% of cysteine, 0.48% of threonine, 0.183% of tryptophan, vitamin A (13 243 IU/kg), vitamin D3 (2 000 IU/kg), vitamin E (81.65 mg/kg), vitamin B1 (4.11 mg/kg), vitamin B2 (7.16 mg/kg), niacin (vitamin B3, 50.22 mg/kg), vitamin B5 (24.29 mg/kg), vitamin B6 (6.11 mg/kg) and vitamin B12 (36 µg/kg), and had unlimited access to water. EPS was preceded by determining a complete blood count, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities, concentrations of urea, creatinine, glucose, magnesium (Mg2+), sodium (Na+), chloride (Cl-), potassium (K+), calcium (Ca2+), as well as by an electrocardiographic and echocardiographic examination.…”
Section: Methodsmentioning
confidence: 99%
“…To this date, normal values for electrocardiographic (ECG) parameters were published for brown hares [5], dogs [6], cats [7], and swine [8], and the reference values for echocardiographic parameters were established for dogs [9], cattle [10], ferrets [11], sheep [12], monkeys [13], Syrian hamsters [14], mice [15], rats [16], and swine [8]. However, despite the widespread use of porcine models in experimental electrophysiology, still no reference values for intracardiac electrical activity and conduction parameters determined during an invasive electrophysiology study (EPS) have been developed in this species thus far.…”
mentioning
confidence: 99%
“…Inflammatory cytokines, 42 inducible NO, 43 and hypoxemia may all result in a maldistributive state, if it were not for the appropriate physiological responses. All dogs maintained a normal MAP, although it may be seen that MAP remained largely within normal limits of 87–127 mm Hg established by Jacobson and colleagues 44–46 …”
Section: Discussionmentioning
confidence: 71%